2020
DOI: 10.1002/asi.24354
|View full text |Cite
|
Sign up to set email alerts
|

The personal information sphere: An integral approach to privacy and related information and communication rights

Abstract: Data protection laws, including the European Union General Data Protection Regulation, regulate aspects of online personalization. However, the data protection lens is too narrow to analyze personalization. To define conditions for personalization, we should understand data protection in its larger fundamental rights context, starting with the closely connected right to privacy. If the right to privacy is considered along with other European fundamental rights that protect information and communication flows, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…After further comparing the 18 sub-criteria, this study found that the most important criterion ranked by IT experts was “avoid harm to others” (GW = 0.113), while the criterion ranked most important by LIS experts was “respect the privacy of others and honor confidentiality” (GW = 0.108), which was slightly higher than “avoid harm to others” (GW = 0.102). The results echoed the findings of the previous studies ( Eskens, 2020 ; Zimmer et al, 2020 ), supporting that informaticists, like the general public, placed the highest value on privacy in information ethics issues.…”
Section: Resultssupporting
confidence: 82%
“…After further comparing the 18 sub-criteria, this study found that the most important criterion ranked by IT experts was “avoid harm to others” (GW = 0.113), while the criterion ranked most important by LIS experts was “respect the privacy of others and honor confidentiality” (GW = 0.108), which was slightly higher than “avoid harm to others” (GW = 0.102). The results echoed the findings of the previous studies ( Eskens, 2020 ; Zimmer et al, 2020 ), supporting that informaticists, like the general public, placed the highest value on privacy in information ethics issues.…”
Section: Resultssupporting
confidence: 82%
“…Related issues, including the privacy, accuracy, property, and accessibility of information, have been widely discussed in previous studies ( Mason, 1986 ; Fallis, 2007 ; Tavani, 2016 ), and the global coronavirus pandemic in the past 2 years has greatly sparked public concerns and attention to information privacy and ethics ( Zimmer et al, 2020 ). With the clearer tension between developing and using technology, the enhancement of information literacy education for all people, especially informaticists’ knowledge and skills of information ethics, has received increasing research and practical attention from the industrial and education sectors ( Stahl et al, 2016 ; Eskens, 2020 ; Fiesler et al, 2020 ; Stark et al, 2020 ; Wu et al, 2020 ). However, the nature, strategies, and pedagogies of ethics education are all parts of a longstanding debate within information and computer science ( Saltz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, choice may be highly artificial when refusal comes at a very high cost for individuals. For instance, it might not even be viable to expect casual news readers to periodically sift through the gigantic amounts of information without use of a recommendation system based on algorithmic models, despite their potentially harmful consequences for privacy and associated rights (Eskens, 2020 , p. 1124). More recently, states such as California (e.g.…”
Section: Approaches To the Protection Of Privacymentioning
confidence: 99%
“…Nevertheless, changing patterns of data creation, use and circulation have made it more challenging to define the purpose of data collection and use from the outset—two important elements to implement privacy-enhancing measures. This means that traditional management strategies such as notice and consent have become increasingly difficult (perhaps even meaningless) to apply (Eskens, 2020 , pp. 1117–1118).…”
Section: Approaches To the Protection Of Privacymentioning
confidence: 99%